El perfil de formación profesional de la secretaria y su impacto en la calidad de servicio a los usuarios - Arbelay Paredes, Maria Andrea (2019)
The present case study was carried out in the Human Talent Department of the Los Ríos Governorate. Which consists of studying the professional training profile of the secretariat and its impact on the quality of service to the user, the problem found the lack of training by the State in quality of service issues, which is a fundamental part of the institution since this serves to improve the services that offer improvement of the care provided to people. Helping efficiently in the development of the work activities of the secretary. The methodology found in the research was the deductive method because it is part of the general to the particular, the descriptive method can also be used, because we can know how the professional training profile has an impact on the quality of service for users, The Research carried out was supported through websites, books and through their own knowledge cited in the development of the research. He analyzed the two variables, which are: professional training profile and quality of service. In this way, the formulation of conclusions that somehow seek to help not only the department but also the institution in general is favored